Baracle® vs Baraclude® for 48 weeks in patients with treatment-naïve chronic hepatitis B: a comparison of efficacy and safety - Kim DY; Kim JH; Tak WY; Yeon JE; Lee JH; Yoon JH; Lee YJ; Lee BS; Han BH; Lee HC (Dove Medical Press, 2017)
Do Young Kim,1 Ju Hyun Kim,2 Won Young Tak,3 Jong Eun Yeon,4 Joon Hyeok Lee,5 Jung Hwan Yoon,6 Youn Jae Lee,7 Byung Seok Lee,8 Byung Hoon Han,9 Han Chu Lee10 1Department of Internal Medicine, Yonsei University College of Medicine, Seoul, 2Department of Gastroenterology, Gachon University Gil Medical Center, Incheon, 3Department of Internal Medicine, Kyungpook National University Hospital, Daegu, 4Department of Internal Medicine, Korea University Guro Hospital, Seoul, 5Department of Gastroenterology, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, 6Department of Internal Medicine, Seoul National University Hospital, Seoul, 7Department of Gastroenterology, Inje University Busan Paik Hospital, Busan, 8Department of Gastroenterology, Chungnam National University Hospital, Daejeon, 9Department of Gastroenterology, Kosin University Gospel Hospital, Busan, 10Department of Internal Medicine, Asan Medical Center, Ulsan University, Seoul, Republic of Korea Background and objective: Entecavir (ETV) is a standard of care for chronic hepatitis B (CHB). In a bioequivalence study, ETV from Dong-A ST (Baracle®) was found to have a pharmacokinetic profile equivalent to ETV from Bristol-Myers Squibb (BMS) (Baraclude®). The present study was conducted to evaluate the antiviral activity and safety of ETV from Dong-A ST in comparison to ETV from BMS in patients with CHB. Methods: In this multicenter, double-blind, active-controlled, stratified-randomized, parallel group, comparative trial, 118 treatment-naïve patients with CHB were randomly assigned to receive either 0.5 mg of ETV from Dong-A ST or ETV from BMS once daily for 48 weeks. The primary efficacy endpoint was virologic improvement (a mean reduction from baseline in serum HBV DNA levels) at 24 weeks. Secondary efficacy endpoints included a mean reduction in serum HBV DNA levels at 48 weeks, proportion of patients with undetectable levels of serum HBV DNA, rates of hepatitis B e antigen (HBeAg) loss and seroconversion, rates of HBsAg loss and seroconversion, and rates of normalization of alanine aminotransferase (ALT) levels. Results: From baseline to week 24, HBV DNA levels (log10) decreased by 4.81 and 4.63 with ETV from Dong-A ST and with ETV from BMS, respectively. The upper limit of two-sided 95% confidence intervals (CI) (equivalent to one-sided 97.5% CIs) for the difference between the treatment groups was 0.208, which was below the noninferiority margin of 1, thus supporting the noninferiority of ETV from Dong-A ST in comparison to ETV from BMS. No statistically significant differences were noted between the treatment groups in all secondary and tertiary efficacy endpoints. Safety profiles were also similar between the two groups. Conclusion: In patients with previously untreated HBeAg-positive or negative HBV infection, the efficacy of ETV from Dong-A ST was noninferior to that of ETV from BMS, and there were no significant differences in efficacy or safety between two groups. Keywords: chronic hepatitis B, generic, ETV from Dong-A ST (Baracle®)